An Insight Into Palestine Politics: Edward Said Vs. Yasser Arafat - Ilyas, Muhammad (Pakistan Languages and Humanities Review, 2025)
The objective of the study is to critically review the ideological perspective by Edward Said concerning the Yasser Arafat leadership in the 1970s 1990s. Yasser Arafat has been known globally as a major player in the Israeli-Palestinian peace process, whereas Edward Said despite his international stature most times criticized the policies of Yasser Arafat. Said is seen as the supporter of resistance movement and secular ideals of democracy whose partial contradictory stand offers a multidimensional ideological stance that has to be examined more properly. The qualitative approach utilized and a critical discourse analysis is carried out on the published text of Edward Said, language, tone, and strategic rhetoric of such an analysis on Arafat is considered. The results highlight that Said was inconsistent in his arguments, so that his critiques, although based on the intellectual truths, could have interfered with the Palestinian political unity when it was needed the most.